The STOP-Bang Test Is Useful for Predicting the Severity of Obstructive Sleep Apnea - Oshita, Hideto (JMA J, 2020)
INTRODUCTION: The STOP-Bang test was used to detect patients at high risk of obstructive sleep apnea (OSA). We evaluated the usefulness of the STOP-Bang test for predicting the severity of OSA in Japanese patients. METHODS: We retrospectively evaluated the patients who performed full polysomnography at the Mihara Medical Association Hospital. We evaluated the correlation between the STOP-Bang score and the apnea hypopnea index (AHI) using Spearman's rank correlation analysis. We then used multivariate analyses to examine the independent risk factor for severe OSA (AHI ≥ 30/hr). RESULTS: One hundred seven patients were diagnosed as no (n = 5), mild (n = 17), moderate (n = 30), and severe (n = 55) OSA. The median age was 67 years old (range: 35-84), and 73 of the 107 patients were males. The correlation coefficient between the STOP-Bang score and AHI was 0.701 (P < 0.001). A STOP-Bang score ≥ 5 had sensitivity of 80.0% and specificity of 76.9% for detecting severe OSA. A STOP-Bang score ≥ 5 and BMI ≥ 30 kg/m(2) were the independent risk factor for severe OSA. CONCLUSIONS: The STOP-Bang score correlates with AHI and is useful for predicting OSA severity. Polysomnography should be performed actively for the patients with high STOP-Bang scores.